Italian Declaration supporting the Berlin Declaration on Open Access to Knowledge in the Sciences and Humanities (2004) - Redazione JLIS.it (JLIS.it, 2012)
The so-called Messina Declaration supporting the Berlin Declaration on Open Access to Knowledge in the Sciences and Humanities was signed by most Italian Universities in 2004.